2018
DOI: 10.1016/j.ejca.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Results of a multicentre randomised controlled trial of cochlear-sparing intensity-modulated radiotherapy versus conventional radiotherapy in patients with parotid cancer (COSTAR; CRUK/08/004)

Abstract: PurposeAbout 40–60% of patients treated with post-operative radiotherapy for parotid cancer experience ipsilateral sensorineural hearing loss. Intensity-modulated radiotherapy (IMRT) can reduce radiation dose to the cochlea. COSTAR, a phase III trial, investigated the role of cochlear-sparing IMRT (CS-IMRT) in reducing hearing loss.MethodsPatients (pT1-4 N0-3 M0) were randomly assigned (1:1) to 3-dimensional conformal radiotherapy (3DCRT) or CS-IMRT by minimisation, balancing for centre and radiation dose of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Similar to the studies above and based on the guidelines-recommendations, all of the historical clinically applied plans included in this planning study not only respected the QUANTEC-criteria, but with Dmean of 29–30 Gy provided mean cochlea doses even lower than previously achieved by Nutting et al [ 30 ] or suggested by Lee et al [ 13 ]. However, as this dose exposure seems to be still associated with considerable side effects for an important percentage of the patients, we aimed to explore the limits of cochlea sparing without jeopardizing PTV coverage or sparing of other important organs as parotids, mandible, optic pathway and spinal cord/brainstem.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar to the studies above and based on the guidelines-recommendations, all of the historical clinically applied plans included in this planning study not only respected the QUANTEC-criteria, but with Dmean of 29–30 Gy provided mean cochlea doses even lower than previously achieved by Nutting et al [ 30 ] or suggested by Lee et al [ 13 ]. However, as this dose exposure seems to be still associated with considerable side effects for an important percentage of the patients, we aimed to explore the limits of cochlea sparing without jeopardizing PTV coverage or sparing of other important organs as parotids, mandible, optic pathway and spinal cord/brainstem.…”
Section: Discussionsupporting
confidence: 65%
“…IMRT in various forms is considered worldwide as standard-of-care for treating nasopharyngeal cancer as it is associated with an increased OS compared to older techniques [ 29 ]. Following the broad implementation of this technique, the phase III trial COSTAR [ 30 ] demonstrated that IMRT for parotideal cancer could reduce the cochlea dose below the formerly accepted tolerance dose of 40–45 Gy to a mean of 35.7 Gy, but this did not lead to a significant reduction of SNHL at 12 months after RT. The authors therefore hypothesized that the previously accepted tolerance dose for cochlea irradiation is too high.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised trial from 2018 evaluated cochlear sparing in the setting of radiotherapy for parotid cancers, and found that cochlear avoidance did not translate into reduced rates of clinically relevant hearing loss. 2 Similarly, the benefits of sparing of swallowing organs at risk are controversial, with some authors arguing that it should not be part of routine clinical practice. 3 The ongoing dysphagia/aspiration at risk structures (DARS) randomised trial is testing the benefits of sparing of swallowing organs at risk on swallowing outcomes.…”
Section: Sparing Of Swallowing-related Organs In Radiotherapy For Oromentioning
confidence: 99%
“…Fortunately, and secondary to anatomic location (parotid and submandibular) and nodal drainage, most major SGCs can be treated with unilateral radiation. Nevertheless, the oral cavity and contralateral salivary glands remain at risk, with rates of grade 2 or higher mucositis—a surrogate for minor salivary gland dose—as high as 77% and acute xerostomia as high as 62%, despite the use of IMRT [ 6 ]. Alternatively, proton beam therapy (PBT) may provide an attractive solution for mucosal toxicity.…”
Section: Introductionmentioning
confidence: 99%